Endoscopic Balloon Dilatation versus Sphincterotomy in Cases of Calcular Obstructive Jaundice during Endoscopic Retrograde Cholangio Pancreatography - Allam, Mohamed Abdel Rasheed Abdel Khalik; Ibrahim, Lotfy Abdelsattar; Allam, Mahmoud Abdel Rasheed Abdel Khalik; Alshabrawi, Hesham (Journal of medical and pharmaceutical sciences, 2017)
Background: - Compared to Endoscopic sphincterotomy (ES), endoscopic balloon dilation (EBD) has been reported to have a lower risk of bleeding but an increased risk of post-ERCP pancreatitis. Additionally, removal of large stones may be challenging when using EBD alone. Patients and methods: - 50 patients with calculary obstructive jaundice was enrolled in our prospective randomized comparative study, ES was done for have of them and EBD for the rest. During ERCP, stone removal was declared as complete if the final cholangiogram showed no residual stones. Clinical evaluation for post ERCP pancreatitis was performed on the following day by symptoms and serum amylase. Results: - There is no statistical significant difference between the two groups, as regard, procedure duration, cannulation trials and time. Success rate was 88% and 80 after ES and EBD respectively. Significant higher rates of endoscopic bleeding were detected with ES. Apart from Significant higher rates of post-ERCP bleeding after ES, no difference was detected between the 2 groups at regard post-ERCP complications. Conclusion: - The efficacy of EBD is similar to ES regarding, removal of common bile duct stones, and it can be safely applied particularly in patients with systemic coagulopathy as it carries a lower rate of Bleeding. Further study evaluating the combined ES and EBD is highly recommended.